Human Complexity vs. Machine Linearity: Tug-of-War Between Two Realities Coexisting in Precarious Balance - Paolo Barile; Clara Bassano; Paolo Piciocchi (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Are machines smarter than humans? What will happen of our species if artificial intelligence (AI) becomes so advanced that it can no longer be controlled? Is the uniqueness of human beings at risk? These are just some of the questions that grip computer science experts as much as ordinary people who experience technological development day in and day out. In our paper, the current scenario will be analysed, from the search for a definition of human intelligence to the historical stages marking the birth and development of technologies capable of emulating many of its facets. The discussion will focus on the main differences between man and machine in the interpretation and replication of the concept of intelligence, highlighting the diversity of approach between an inherently complex entity (man) and a linearly functioning system (machine). The purpose will be trying to provide insights to answer the initial questions, by analysing possibilities and limitations of the main AI emulation techniques. The optimistic view offered by our work suggests that the machine's highest aspiration can only come down to the sheer emulation of our behaviours: machines' linearity will always remain in the service of human complexity, never vice versa.